PTU-198 Serum FGF19 Levels are Related to Disease Activity in Ileal Crohn'S Disease. (4th June 2013) - Nolan, J D; Johnston, I; Dew, T; Pattni, S; Walters, J R
Abstract : Introduction: FGF19 is a polypeptide hormone produced in the ileum. It's transcription is stimulated by bile acid (BA) activation of the Farnesoid X receptor (FXR). In human cell lines the transcription of FGF19 is suppressed by pro inflammatory cytokines (TNF-α, IL-1β) via inhibitory effects on 'FXR'. We hypothesised that circulating FGF19 levels will be low in patients with active ileal Crohn's disease and that these levels will increase after the administration of anti-inflammatory treatments commonly used to induce clinical remission. Methods: Fasting circulating FGF19 levels were measured using ELISA. Disease activity was assessed using the Harvey Bradshaw index. In a cross sectional study, 30 patients with Crohn's disease involving the ileum (and no previous intestinal resections) were recruited, 12 with active disease (HBI > 4) and 8 with inactive disease. In longitudinal studies, 4 patients with active colonic disease and 5 patients with active disease involving the ileum had samples taken whilst their disease was active and again during medically induced clinical remission (HBI < 4 induced by corticosteroids or anti-TNF) over 6 weeks later. 6 patients with CD involving the ileum (5 with previous ileal resection) whose disease remained inactive, had FGF19 levels samples measured taken on 2 separate occasions over 6 weeks apart. Non parametric statistical tests were used (Mann whitney, medians and ranges shown). Results: In the cross sectional study serum FGF19 levels were significantly lower in those patient with CD involving the ileum with active disease (median 40, 3- 338) compared to inactive disease (median 147, 46 –255, p = 0.0486). In the longitudinal studies, serum FGF19 levels were significantly lower in the patients with CD involving the ileum whilst their disease was active (median 35, range 3 – 54) compared to paired levels taken after medically induced remission (median 141, range 116 – 184, p = 0.002). Paired FGF19 levels were not statistically different in the 4 patients with colonic Crohn's disease during active disease (median 105, range 36 – 151) compared to medically induced clinical remission (median 86, range 40 – 120, p = 0.48). There was no significant difference in paired FGF19 levels In the 6 patients with CD involving the ileum with inactive disease taken on 2 seperate occasions (5 with previous ileal resections). Conclusion: Circulating FGF19 levels are lower during active ileal or ileo-colonic crohn's disease and increase after medically induced clinical remission. FGF19 levels may be induced by anti-inflammatory treatments either as a result of the inhibition of inflammtory cytokines within the ileum or due to enhanced BA absorption post treatment. Disclosure of Interest: None Declared.